2021
DOI: 10.3389/fmicb.2021.681251
|View full text |Cite
|
Sign up to set email alerts
|

A Significantly High Abundance of “Candidatus Liberibacter asiaticus” in Citrus Fruit Pith: in planta Transcriptome and Anatomical Analyses

Abstract: Huanglongbing, a highly destructive disease of citrus, is associated with the non-culturable phloem-limited α-proteobacterium “Candidatus Liberibacter asiaticus” (CLas). The distribution patterns of CLas in infected plant are variable and not consistent, which make the CLas detection and characterization more challenging. Here, we performed a systemic analysis of CLas distribution in citrus branches and fruits of 14 cultivars. A significantly high concentration of CLas was detected in fruit pith (dorsal vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(67 reference statements)
0
8
0
Order By: Relevance
“…In vivo transcriptomic analyses are required to understand the active pathways in C Las. A recent study identified the regions in the citrus fruit pith with higher bacterial titers which was used to conduct RNA-seq analysis after rRNA removal ( Fang et al, 2021 ). This study compared the gene expression profiles of the fruit pit vs. leaf midribs and found different gene expression profiles related to virulence genes; however, the resolution of the transcriptome profile was lower in midribs compared to fruit pit mainly due to the lower bacterial titers ( Fang et al, 2021 ).…”
Section: New Approaches For Studying Mechanisms Against Uncultured Ba...mentioning
confidence: 99%
“…In vivo transcriptomic analyses are required to understand the active pathways in C Las. A recent study identified the regions in the citrus fruit pith with higher bacterial titers which was used to conduct RNA-seq analysis after rRNA removal ( Fang et al, 2021 ). This study compared the gene expression profiles of the fruit pit vs. leaf midribs and found different gene expression profiles related to virulence genes; however, the resolution of the transcriptome profile was lower in midribs compared to fruit pit mainly due to the lower bacterial titers ( Fang et al, 2021 ).…”
Section: New Approaches For Studying Mechanisms Against Uncultured Ba...mentioning
confidence: 99%
“…Host responses against C Las infections vary in different tissues of same plants. The virulence, stress response, and antimicrobial secondary metabolites-associated genes show enhanced expression in midrib tissues from the leaves compared to the fruit piths in HLB-positive Citrus reticulata Blanco “Shatangju” [ 150 ]. Similarly, the temporal host response may vary in citrus against C Las infestation.…”
Section: Host Responses To C Las Infectionmentioning
confidence: 99%
“…), a holoparasitic plant, from one infected citrus plant to other citrus plants or other amenable hosts, e.g., periwinkle ( Catharanthus roseus (L.) G. Don) [ 2 ]. CLas can infect most commercial citrus cultivars and present as an uneven distribution pattern within infected citrus plants [ 3 , 4 ]. The distribution pattern of CLas in infected citrus trees could be different, mainly due to the different cultivars and degrees of disease severity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The distribution pattern of CLas in infected citrus trees could be different, mainly due to the different cultivars and degrees of disease severity [ 5 , 6 ]. However, an investigation of CLas distribution in 14 commercial citrus cultivars showed that a significantly high abundance of CLas was stably observed in fruit pith tissue compared to other tissues from the individual citrus branch [ 4 ].…”
Section: Introductionmentioning
confidence: 99%